Penerapan Pemasaran Digital pada UMKM Indah Donat di Bengkalis - Oby, Muhammad; Bustami Bustami; Nofiar.Am, Andri; Hadi, Larbiel; Akbar, Rahmad (Politeknik Kampar, 2025)
The digital era has transformed human lifestyles and demands rapid adaptation across various sectors, including Micro, Small, and Medium Enterprises (MSMEs). MSMEs play a strategic role in Indonesia’s economy as labor absorbers and developers of local products. However, limited digital literacy and skills often hinder their utilization of digital marketing. This community service program aims to enhance the capacity of the “Indah Donat” MSME in Bengkalis through guidance in implementing digital marketing strategies. The participatory approach includes initial surveys, needs assessment, development of a digital marketing framework, promotion via Google My Business, social media, and online marketplaces, as well as sustainability evaluation. The results show improved capabilities of the partner in managing digital content, expanding market reach, and increasing sales. “Indah Donat” now has an integrated online business profile, structured content calendar, and distribution channels through social media and marketplaces. This approach aligns with the Technology Acceptance Model (TAM) and modern marketing concepts based on Segmenting, Targeting, and Positioning (STP). In conclusion, the program effectively enhances MSME digital capacity, broadens marketing networks, and strengthens business independence, while contributing to digital transformation and local economic empowerment.